Prevalence of nosocomial infections in the intensive care unit - Durgad, Ambanna Gowda; Varadarajan, Sudarshan (International Journal of Research in Medical Sciences, 2017)
Background: ICU patients are at risk for acquiring nosocomial infection. The present study is to define, underlying disease, severity of illness, of nosocomial infections in ICU patients .Patients hospitalized in the ICU’s are 5 to 10 times more likely to acquire nosocomial infections than other hospital infections. The frequency on infections at different anatomic sites and the risk of infection vary by the type of ICU. The main objective of research is to study the prevalence of nosocomial infections in the ICU and to find out the predominant organism causing. Methods: A total of 100 cases developing infection after 48 hours after admission into intensive care unit were studied. Study design – Prospective study for one year. Sample size – 100 cases will be included in the study with detailed history, physical examination and required lab investigations. Results will be analysed statistically. Results: Among 100 patients who had nosocomial infections in the ICU, (28)28% had UTI, (22) 22% LRTI, (20)20% CRBSI, (16)16%Soft tissue infections & (14) 14% had Pneumonias. Among 14 cases of Pneumonias 10 were associated with VAP. This study also reveals that 62(79.48%) were due to device related and 16(20.51%) were non device related. Gram negative aerobes were the predominant organisms isolated in this study and appropriate antibiotic were substituted on Culture sensitivity reports. The mean age of the patients was 46.22 years ranging from (21 to 80 years), there were 66 males (66%) and 34 females (34%) in this study. Out of 50 patients, 16 (32%) were on ≥2 antibiotics. The mean days of use of antibiotics were 10 days. Mean days of stay in ICU was 6.42 days. Out of 100 patients, 22 (22%) had DM, 48(48%) had HTN and 30(30%) had related Co-morbidities. Conclusions: NIs is seen worldwide but is less studied and are given less emphasis in developing countries. This study reports various types of Nosocomial Infections in the ICU set up. The relatively high incidence of NI observed in this study may be a reflection of the higher severity of illness, poor nutritional status, more interventions poor handling by staff and possibly poor adherence to aseptic measures. The ICU of low resource country may have to cope up with patients with severe illness coupled with lack of resources and expertise and control the nosocomial infection.